Чтобы помнили... - Демышева Наталья Николаевна (2017)
Титульный лист по Брайлю, заглавие дано с обложки Экземпляры: БС (20170606) / Инвентарный номер: РТШ54594 / Сис.шифр: 63.3(2)622.78 / Авт.знак: Ч-80 / ГРНТИ: 03.23 / ББК: 63.3(2)622,88